Tinjauan Pengelolaan Piutang pada PT. Sarana Cipta Unggul - Natasha Marnafa Setiawan Seputri; Yayuk Nurjanah (Jurnal Aplikasi Bisnis Kesatuan, 2023)
ABSTRACTReceivables are one component of assets that determine the smooth running of a company's operations. In the balance sheet reported in assets. Receivables are liquid current assets because they can be turned into cash immediately, namely within a maximum period of one year. In addition, the amount of company receivables in one period is generally quite material, so that the administration of the recording and presentation must be carried out properly, in accordance with the provisions stipulated in generally accepted financial accounting principles.The purpose of this review is to be able to find out how the policies regarding receivables are and find out how the policies and management of receivables are at PT Sarana Cipta Unggul which is engaged in renting forklifts and heavy equipment. The results of the review show the policy regarding receivables at PT. Sarana Cipta Unggul with the classification of trade receivables, other receivables, employee receivables and Affiliate receivables.The accounting treatment of accounts receivable at PT Sarana Cipta Unggul is actually in accordance with the company's Standard Operating Procedure. This is evidenced by the recognition of receivables by recording leases and receivables income with complete documents. In addition, there is also an aging analysis of receivables. But it still needs to be improved because the average calculation of accounts receivable is still 182.5 days. This indicates that the rotation is running slowly. This means that the collection section is still not working optimally or there are still a lot of bad debts. It is suggested to PT Sarana Cipta Unggul to review its receivables policy to minimize bad debts and to further improve its collection performance.. Keywords: Receivables, Accounts Receivable Policy, Receivable Constraints